WE5.8 Length of stay in Emergency General Surgery – Time for a Comprehensive Look at Our Elderly Population. (9th August 2022) - Howie, Emma; Helley, Michael; Box, Emma; Watt, David
Abstract: Aims: Patients' Length of stay (LoS) has increased due to increasing age and co-morbidities. The British Geriatric Society 2020 Position statement states patients >65 being considered for laparotomy should have a documented Clinical Frailty Scale (CFS) within 72hrs of admission and, if >5, should receive Geriatrician lead Comprehensive Geriatric Assessment (CGA) which improves patient outcomes. We sought to quantify CFS documentation in Emergency General Surgery (EGS) patients in a District General Hospital before implementing a new CGA to improve elderly EGS patient care. Methods: Planning: Business intelligence records of all adult EGS admissions over 1-year were retrospectively interrogated – comparing LoS between age groups, comorbidity number, discharge destination and whether a procedure was undertaken. EGS admissions were prospectively reviewed over 1-month, noting patients >65 and CFS documentation. Results: Retrospective: 3962 patients >16 were admitted January-December 2019. 1317 patients (33%) were >65. Average LoS was 3.9 days, overall highest LoS was ages 75–84 (8.5 days). Highest average LoS were >75yr olds requiring supported care at home (15.5 days). LoS varied directly with number of diagnosis codes and increased if undergoing a procedure. Prospective: There were 130 EGS admissions in 1 month, 53 (40%) patients were >65. No patients >65 had a CFS documented. Conclusions: Increased LoS in EGS is associated with increasing age and comorbidities - particularly patients > 75 awaiting home-care. BGS statement concordance to establish prompt frailty assessment is imperative to improve patient outcomes. Staff education and surgery-specific CGA note-stickers may improve concordance. Subsequent analysis to evaluate effectiveness in patient and economic outcomes is paramount.